A Psycholinguistic Analysis of Students’ Speaking Anxiety Among Eight Graders at SMP Negeri 2 Kunjang - Fandi Andreas Setiawan; Elisa Nurul Laili (Institut Teknologi Pendidikan Indonesia, 2026)
This study aims to analyze psycholinguistic factors contributing to English-speaking anxiety and its effect on the speaking ability of eighth-grade students in class VIII B at SMP Negeri 2 Kunjang. Speaking anxiety is considered an affective factor that may interfere with cognitive processes in language production, including speech planning, vocabulary retrieval, and speech fluency. This research employed a descriptive qualitative design with a psycholinguistic perspective. The participants were 31 students of class VIII B and one English teacher as a supporting informant. Data were collected through classroom observation, a questionnaire based on the Foreign Language Classroom Anxiety Scale (FLCAS), and semi-structured interviews. The data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing and verification. The findings indicate that speaking anxiety is influenced by psycholinguistic factors such as fear of making mistakes, lack of self-confidence, limited vocabulary, and cognitive overload during speech production. These factors affect students’ speech performance, particularly in speech planning, lexical retrieval, and fluency. Students with high anxiety tend to show hesitation, long pauses, and avoidance of speaking activities in the classroom.It can be concluded that speaking anxiety significantly affects students’ English-speaking ability through psycholinguistic mechanisms involving both cognitive and affective processes in language production.